A Survey on Students' Confidence in Reading Physics Research in English - Putri, Nabila Trijanuary; Wahyuni, Dini Nur Indah; Wulandhary, Putri; Wahyunengsih, Wahyunengsih (DIKSI: Jurnal Kajian Pendidikan dan Sosial, 2025)
By assessing the reading confidence levels of physics students, this study investigates the primary obstacles influencing their understanding of English-language research publications. A structured questionnaire measuring four aspects of reading confidence scientific vocabulary and terminology, comprehension of research article structure, application of reading strategies, and critical reading and interpretation was used to gather data from 64 physics students using a quantitative descriptive approach. The findings show that students had a moderate level of trust in their ability to understand scientific terminology (M = 3.32–3.34), indicating that comprehension is nevertheless hampered by new technical jargon. Meanwhile, students reported a high level of confidence in identifying research structures, applying reading strategies, and performing critical interpretation (M = 3.4 However, this confidence was not always accompanied by a thorough understanding of scientific material. These results suggest that limited mastery of scientific terminology and the complexity of academic language significantly contribute to students’ reading difficulties. In order to boost discipline-specific vocabulary, enhance students' comprehension of English-language physics research articles, and improve reading skills, this study suggests implementing more focused English for Specific Purposes (ESP) education.